The RACOON viral pneumonia score for structured reporting of pre-existing, acute, and post-pneumonic findings on chest CT - Thorsten Persigehl; Philipp Fervers; Andreas Bucher; Peter Isfort; Peter Isfort; David Maintz; Tobias Penzkofer; Marwin Sähn; Thomas Vogl; Jonathan Kottlors; Felix Doellinger (Frontiers in Medicine)
BackgroundThe multi-dimensional RACOON Viral Pneumonia Score (RVPS) was developed to compensate for the main weaknesses of the established one-dimensional chest computed tomography (CT) scores. It aimed to quantify the severity of pneumonia and qualitatively monitor infectious lung disease from the acute stage to post-pneumonic sequelae.ObjectivesThis research focuses on the original development and evaluation of applicability and inter-reader reliability of the RVPS.MethodsWithin the Radiological Cooperative Network (RACOON), the scoring system was developed after several expert meetings and tested in this proof-of-concept study with 8,525 observations. In the subset of inter-reader validation (7,800 observations), eight blinded radiologists applied the RVPS and evaluated the following CT findings for each lung lobe individually: (I) pure ground glass opacities (GGO), (II) GGO and interstitial thickening, (III) consolidations, (IV) linear opacities and reticulations, and (V) fibrotic-like changes. The extent of each pathology was scored on a scale of 0–5 points, and the total involvement was calculated. Inter-reader variability was assessed using Kendall’s W.ResultsOverall inter-reader reliability of the RVPS was excellent (Kendalls’ W 0.95). CT findings associated with acute pneumonia were scored with good agreement (W 0.81-0.87). Moderate uncertainty was introduced when separating category IV vs. category V findings (W 0.55-0.69). The overall extent of post-infectious findings was assessed with good agreement (W 0.79). The longitudinal distribution of subscores allowed for differentiation between acute pneumonia and post-pneumonic sequelae.ConclusionThis study presents the RVPS as a comprehensive tool for inter-reader reliable evaluation, longitudinal monitoring, and structured documentation of the extent as well as quality of chest CT findings in infectious lung disease.